Philip Gould
XI, 187 p.
Keywords: The death of Philip Gould, former Labour Party Communications Director, in 2011 deprived Britain of one of its most acute and well-respected political minds. In this book his friends and colleagues including David Miliband and Lord Mandelson discuss his life from his early years in the Labour Party to his ultimately doomed fight against cancer.